HUBUNGAN ANTARA KECEPATAN, VOLUME DAN KEPADATAN LALU LINTAS RUAS JALAN SILIWANGI SEMARANG - Nugroho Julianto, Eko (Semarang State University, 2010)
Abstract: The volume of traffic traveling on roads Siliwangi have increased from year to year. ThisisÃ‚Â dueÃ‚Â toÃ‚Â theÃ‚Â developmentÃ‚Â ofÃ‚Â thisÃ‚Â area. To overcomeÃ‚Â the problemÃ‚Â ofÃ‚Â trafficÃ‚Â congestion onÃ‚Â these roadsÃ‚Â isÃ‚Â requiredÃ‚Â priorÃ‚Â knowledgeÃ‚Â aboutÃ‚Â trafficÃ‚Â characteristicsÃ‚Â andÃ‚Â modelÃ‚Â ofÃ‚Â theÃ‚Â relationship between these characteristics. This study aims to analyze the model of the relationship between the characteristic volume (V), speed (S) and density (D)Ã‚Â traffic, in accordance with existing conditions. Survey dataÃ‚Â includesÃ‚Â traffic volumes and speeds withÃ‚Â the manual count method, being analytical modelsÃ‚Â includeÃ‚Â modelsÃ‚Â Greenshield,Ã‚Â Greenberg,Ã‚Â andÃ‚Â Underwood.Ã‚Â TheÃ‚Â resultsÃ‚Â showedÃ‚Â thatÃ‚Â the relationship model that is suitable for VSD Siliwangi road is to follow the model of Underwood with r = 0859, with the model of Us = 68.20 x exp(-D/-15.05). Keywords: relationship model, Greenshield, Greenberg, Underwood Ã‚Â Abstrak: Volume perjalanan lalu lintas pada ruas jalan Siliwangi mengalami peningkatan dari tahun keÃ‚Â tahun.Ã‚Â HalÃ‚Â iniÃ‚Â disebabkanÃ‚Â perkembanganÃ‚Â daerahÃ‚Â ini.Ã‚Â UntukÃ‚Â mengatasiÃ‚Â masalahÃ‚Â kemacetan lalulintasÃ‚Â padaÃ‚Â ruasÃ‚Â jalanÃ‚Â iniÃ‚Â terlebihÃ‚Â dahuluÃ‚Â diperlukanÃ‚Â pengetahuan mengenaiÃ‚Â karakteristikÃ‚Â lalu lintasÃ‚Â dan modelÃ‚Â hubunganÃ‚Â antarÃ‚Â karakteristikÃ‚Â tersebut. KajianÃ‚Â iniÃ‚Â bertujuan menganalisis model hubunganÃ‚Â antarÃ‚Â karakteristikÃ‚Â volumeÃ‚Â (V),Ã‚Â kecepatanÃ‚Â (S)Ã‚Â danÃ‚Â kepadatanÃ‚Â (D)Ã‚Â laluÃ‚Â lintas,Ã‚Â sesuai dengan kondisi yang ada. Survai data meliputi volume dan kecepatanÃ‚Â laluÃ‚Â lintas dengan metode manualÃ‚Â count,Ã‚Â sedangÃ‚Â analisis model meliputi modelÃ‚Â Greenshield,Ã‚Â Greenberg,Ã‚Â danÃ‚Â Underwood. Hasil analisis menunjukkan bahwa model hubungan V-S-D yang sesuai untuk ruasÃ‚Â jalan Siliwangi adalah mengikuti model Greenberg dengan nilaiÃ‚Â r = 0.773, dengan model Us = 68.20 x exp(-D/-15.05). Kata kunci: model hubungan, greenshield, greenberg, underwood